Efek pemediasi modal intelektual pada ketidakpastian lingkungan, strategi inovasi dan kinerja organisasi - Fitri Romadhon; Erlina Diamastuti (Universitas Negeri Malang, 2020)
This study aims to examine the effect of environmental uncertainty on innovation strategies and organizational performance, and when combined with intellectual capital as variable that mediate innovation strategies and organizational performance. The research approach used is a quantitative approach through a survey method. The research was carried out by disseminating questionnaires to 55 respondents. Data analysis technique uses partial least square technique, which is preceded by testing the instrument, inner and outer models. The results show that all hypotheses were supported. Environmental uncertainty can determine innovation strategies establishment and organizational performance. Meanwhile, the innovation strategy developed by the company can affect organizational performance. In addition, intellectual capital is proven to mediate innovation strategies and organizational performance, thus it can be inferred that innovation strategies become a fruitful factor in improving performance if supported by intellectual capital. This study is inseparable from a number of limitations, such as not involving other variables that can determine organizational performance, the low participation of respondents, so further research is expected to expand the research sample and consider other determinants, for instance management accounting systems, management control systems Keywords: Environmental Uncertainty, Innovation Strategy, Intellectual Capital, Organizational Performance